Perceptions of the Impact of Social Media on College Student Engagement at Historically Black Colleges and Universities - Parrott, Acquanetta S.; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2024)
This research study explored the impact of social media on college students’ engagement at Historically Black Colleges and Universities (HBCUs). The study used a qualitative methodology to examine how social media influences students’ social experiences, classroom engagement, and academic achievement. George Kuh’s Student Engagement Theory was used as the theoretical framework. Data from interviews with 20 undergraduate students from two HBCUs in Mississippi revealed that social media enhanced social connectivity and campus involvement. However, social media had a dual impact on classroom engagement, promoting collaboration while risking distraction. The findings identified nine themes from the perceived impact of social media on college students’ social experiences, classroom engagement, and academic achievement at HBCUs in Mississippi. The study’s significance underscored the need for strategies to leverage the benefits of social media while mitigating drawbacks and providing valuable insights for educators and policymakers in higher education.